EVALUASI TEKNIK PENYULUHAN FASILITASI BALAI PENYULUHAN PERTANIAN PERIKANAN DAN KEHUTANAN (BP3K) DALAM PENERAPAN JAJAR LEGOWO DI KECAMATAN TERAS KABUPATEN BOYOLALI - Dicky Alfrima Faqtoni; Bekti Wahyu Utami; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2019)
The Agricultual Extension, Fisheries and Forestry Center facilitation aims to support accelerated national strategic food production.One of intensification national food production intended to intensifiction rice production. The effort intensifiction rice production directed to applying jajar legowo plantation techniques. This study aims to examine the components of extension techniques effectiveness applying jajar legowo plantation by agricultural extension center in Teras District. This research used basic method is descriptive qualitative. Location determination of this research is purposive. The sampling technique used purposive sampling technique.The results of this research show that (1) The implementation of extension techniques in Teras district from the context aspect is good and adequate; (2) The implementation of extension techniques seen from the input aspect is good and adequate; (3)The implementation of extension techniques in seen from the process aspect is good; (4) The implementation of extension techniques from the product aspect is good and successful; (5) The effectiveness of extension techniques is good, it was proved by the increase of province and productivity